2018
DOI: 10.1159/000489654
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Polymorphisms of the Complement 3 Gene and Schizophrenia in a Han Chinese Population

Abstract: Background/Aims: Schizophrenia is a severe psychiatric disorder, and complement 3 (C3) is closely related to schizophrenia. We investigated the association between C3 polymorphisms and schizophrenia in a Northeast Han Chinese population. Methods: A total of 2240 Chinese people, consisting of 1086 patients with schizophrenia and 1154 healthy controls, were recruited for this study. Ten single nucleotide polymorphisms (SNPs; rs11569562, rs344555, rs2241393, rs2241392, rs11569514, rs445750, rs451760, rs11672613, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…In the present study, we explored the relationship between variants of the C3 gene and the susceptibility to CAD and lipid levels by tagSNPs in a Chinese population. In recent years, two studies were conducted to explore the association between polymorphisms of the Complement 3 gene and diseases in Chinese Han populations [29, 30]. We found the frequencies of alleles in controls in the present study were similar to those in their studies.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, we explored the relationship between variants of the C3 gene and the susceptibility to CAD and lipid levels by tagSNPs in a Chinese population. In recent years, two studies were conducted to explore the association between polymorphisms of the Complement 3 gene and diseases in Chinese Han populations [29, 30]. We found the frequencies of alleles in controls in the present study were similar to those in their studies.…”
Section: Discussionsupporting
confidence: 85%
“…Some studies found an association with some SNPs of DRD2 gene with SCZ [ 9 , 25 , 26 , 27 , 52 , 53 , 54 ], whereas Zhang et al. found no association of DRD2 polymorphism with SCZ [ 55 ]. An association of rs1079727, rs2283265, rs1124492 SNPs with SCZ was found in the Han Chinese population living in Taiwan [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher C4 levels were likewise detected in the CSF of patients with schizophrenia [ 82 ]. The SNVs of the C3 gene with protective or harmful effects regarding schizophrenia onset were identified by a study that recruited more than 2000 Han Chinese individuals [ 83 ]. C3 mRNA expression was upregulated in the PFC of those that demonstrated depression followed by suicide [ 84 ].…”
Section: Microglia–synapse Interaction In Schizophreniamentioning
confidence: 99%